Pengaruh Fleksibilitas Kerja, Otonomi Pekerjaan, Lingkungan Kerja dan Budaya Inklusif Terhadap Motivasi Kerja di Moderasi Self-efficacy Pada Gen Z (Studi Kasus: Tenaga Kerja Gen Z Jawa Barat) - Setiawan, Jodi; Rony, Zahara Tussoleha; Faeni, Dewi Puspaningtyas (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to analyze the effect of Work Flexibility, Job Autonomy, Work Environment, and Inclusive Culture on Work Motivation with Self-efficacy as a moderating variable. The sampling method used was purposive sampling, with a sample size of 384 respondents from generation Z. Data processing was carried out using statistical tests with SmartPLS 4.1. The results showed that Work Flexibility, Job Autonomy, Work Environment, and Inclusive Culture have a positive and significant effect on Work Motivation. In addition, Self-efficacy significantly strengthens the relationship between Work Flexibility and Work Motivation. However, Self-efficacy does not have a significant effect in strengthening the relationship between Job Autonomy, Work Environment, and Inclusive Culture with Work Motivation.